The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s12576-017-0522-3
|View full text |Cite
|
Sign up to set email alerts
|

Facial skin blood flow responses during exposures to emotionally charged movies

Abstract: The changes in regional facial skin blood flow and vascular conductance have been assessed for the first time with noninvasive two-dimensional laser speckle flowmetry during audiovisually elicited emotional challenges for 2 min (comedy, landscape, and horror movie) in 12 subjects. Limb skin blood flow and vascular conductance and systemic cardiovascular variables were simultaneously measured. The extents of pleasantness and consciousness for each emotional stimulus were estimated by the subjective rating from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 36 publications
2
26
0
Order By: Relevance
“…We have reported that the changes in facial skin blood flow may serve as a more sensitive tool to assess an emotional or mood status in humans (Matsukawa et al. ). In this study, we aimed to examine whether prefrontal neural activity has positive correlation with the changes in facial skin blood flow during emotionally charged stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have reported that the changes in facial skin blood flow may serve as a more sensitive tool to assess an emotional or mood status in humans (Matsukawa et al. ). In this study, we aimed to examine whether prefrontal neural activity has positive correlation with the changes in facial skin blood flow during emotionally charged stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Matsukawa et al. () found no significant changes in hand skin blood flow and vascular conductance during any of emotional movie challenges (comedy, landscape, and horror), although forearm skin blood flow and vascular conductance decreased during exposure to comedy and/or horror movies. In this study, most systemic cardiovascular variables failed to alter significantly during exposure to any of the emotionally charged movies, although slight increases in HR and CO and a slight decrease in TPR were observed during exposure to a horror movie (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations